ANTI-INFLAMMATORY EFFECTS OF PROPOXAZEPAM ON DIFFERENT MODELS OF INFLAMMATION - Golovenko, N. Ya.; Kabanova, T. A.; Andronati, S. A.; Halimova, O. I.; Larionov, V. B.; Reder, A. S. (International Journal of Medicine and Medical Research, 2020)
Background. Propoxazepam, 7-bromo-5-(2-chlorophenyl)-3-propoxy-1H-benzo[e][1,4]diazepin-2(3H)-one, is a promising analgesic and anticonvulsant and is on preclinical trial. Objective. The aim of the research was to study the anti-inflammatory and analgesic action of Propoxazepam. Methods. The anti-inflammatory action was evaluated by carrageenan induced rat paw edema, formalin-induced paw licking response in mice and bradykinin-induced pain response in rat models. Results. It was established for the first time that the administration of Propoxazepam caused a significant anti-inflammatory activity when tested in different in vivo chemical experimental models of induced inflammation, i.e. carrageenan-, bradykinin- and formalin-induced inflammation tests. Conclusions. Propoxazepam significantly reduced acute and sub-acute inflammation and proved its efficacy and similar to anti-inflammatory action.